ANALSIS DEBIT DI SPILLWAY AMONGGEDO AKIBAT SEDIMENTASI - Alkadri, Alkadri (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
Cycle of Hidrologi, that is current of sea level to atmosphere later; then surface of land;ground and back again to sea which have never desisted. Movement irrigate above surface of land; ground one of them in river. Speed of current when high rainfall in river of anggapoa at pate; upstream barricade amonggedo can bubble up, so that some of stream pointed at spillway. Functioning Spillway as building of abundance. This research aim to to analyse the level of debit residing in amonggedo spillway which in resulting the existence of sedimentation Result of from debit analysis which in earning is maximum debit pursuant to period repeat: (2 Year= 139 m3 / det (5 Year = 167 m3 / det), ( 10 Year = 203 m3 / det), (20 Year = 256 m3 / det),( 25 Year = 257 m3 / det), ( 50 Year = 280 m3 / det), (100 Year = 357 m3 / det). Sediment volume that happened at Amonggedo spillway = 1.229,29 m3